Peningkatan Hasil Belajar Matematika Tentang Pecahan Melalui Pendekatan Matematika Realistik di Kelas IV - Ratih Purnamasari (Pedagogia: Jurnal Ilmiah Pendidikan, 2016)
The aim of the research is to improve the learning outcome of mathematics on fraction through the application of realistic approach. The research was conducted to 24 students of the fourth grade at SDN Cilendek Timur 2 Bogor. The research method employed was Classroom Action Research with the model Kemmis and Taggart which consists of four steps: planning, acting, observing, and reflecting. The research was undergone in three cycles. The result research shows that there is improvement of the learning result on fraction. In the first cycle, the percentage of students getting the score of 70 or higher was 12.5%, in the second cycle, it reached 56.5%, and in the third cycle it was 92%. The students and teacher’s activities were in accordance with realistic approach reaching 92.5% at the end of the third cycle. Therefore, it can be inferred that the application of realistic approach is able to improve students’ learning outcome on fraction. Thus it is recommended that teachers use realistic approach as one of the alternatives to teach mathematics, especially on fraction.